Qualidade física e química de solos após aplicação de biochar - Nunes, Marcos Euzébio (2017)
New systems and new production technologies that are appropriate to different environmental conditions, combining food production with the preservation of soil and water biodiversity, is necessary in the field of research, to offer alternatives to productive systems. Several works in the literature report Biochar's potential to improve soil physical and chemical attributes, thus contributing to increased crop yeelds and environmental conservation. However there are still several issues to be elucidated regarding the interaction of this material in productive environments. The objective of this study was to evaluate the physical and chemical attributes of a sandy loam Plinthosol after seven years of Biochar incorporation and the physical attributes of a medium textured Red Latosol after nine years of Biochar incorporation combined or not fertilizers. The experimental design was a randomized complete block design in a 4 x 4 factorial scheme with four replicates, composed of (0 kg ha-1 ; 100 kg ha-1 ; 200 kg ha-1 and 300 kg ha-1 of NPK) and (0 Mg ha-1 ; 8 Mg ha-1 ; 16 Mg ha-1 and 32 Mg ha-1 of Biochar) for the experiment in Plinthosol. In the Latosol the experimental arrangement was in a 2 x 5 factorial scheme with four replicates, composed of (0 kg ha-1 and 300 kg ha-1 of NPK) and (0 Mg ha-1 ; 2 Mg ha-1 ; 4 Mg ha-1 , 8 Mg ha-1 and 16 Mg ha-1 of Biochar). For Plinthosol, it was verified that the application of Biochar in the unfertilized soil gave rise to large pores, which led to the increase of macroporosity, thus reducing soil density. However, soil microporosity was not altered, resulting in 9% gains in available water, and cation exchange capacity. On the other hand, in the treatments that received only fertilizations, it was verified reductions in the density and resistance of the soil to penetration, and increase mainly in the total porosity and S-Index. For Latosol it was verified that the application of Biochar in the soil did not condition changes in the physical attributes until the dose tested. On the other hand, in the treatments that received only fertilizations it was verified reductions in the total porosity and saturation humidity, however this reduction is not enough to compromise the vegetal development. The results suggest that the effect of Biochar remains on the Plintossolo with seven years of application, regarding macroporosity increase and cation exchange capacity, however the substantial increases verified in initial evaluations in available water was not observed. On the other hand, it is observed that the Biochar does not alter the attributes of Haplustox nine years after the application under the conditions tested.